Differences in Therapeutic Responses and Factors Affecting Post-Stroke Depression at a Later Stage According to Baseline Depression - Lee, Eun-Jae (J Stroke, 2018)
BACKGROUND AND PURPOSE: The pathophysiology of post-stroke depression (PSD) is complex and may differ according to an individual’s mood immediately after stroke. Here, we compared the therapeutic response and clinical characteristics of PSD at a later stage between patients with and without depression immediately after stroke. METHODS: This study involved a post hoc analysis of data from EMOTION (ClinicalTrials.gov NCT01278498), a placebo-controlled, double-blind trial that examined the efficacy of escitalopram (10 mg/day) on PSD and other emotional disturbances among 478 patients with acute stroke. Participants were classified into the Baseline-Blue (patients with baseline depression at the time of randomization, defined per the Montgomery-Asberg Depression Rating Scale [MADRS] ≥8) or the Baseline-Pink groups (patients without baseline depression). We compared the efficacy of escitalopram and predictors of 3-month PSD (MADRS ≥8) between these groups. RESULTS: There were 203 Baseline-Pink and 275 Baseline-Blue patients. The efficacy of escitalopram in reducing PSD risk was more pronounced in the Baseline-Pink than in the Baseline-Blue group (p for interaction=0.058). Several risk factors differentially affected PSD development based on the presence of baseline depression (p for interaction <0.10). Cognitive dysfunction was an independent predictor of PSD in the Baseline-Blue, but not in the Baseline-Pink group, whereas the non-use of escitalopram and being female were more strongly associated with PSD in the Baseline-Pink group. CONCLUSIONS: Responses to escitalopram and predictors of PSD 3 months following stroke differed based on the presence of baseline depression. Our data suggest that PSD pathophysiology is heterogeneous; therefore, different therapeutic strategies may be needed to prevent PSD emergence following stroke.